An Emerging Leadership Model for Millennial Educators - Cinderella C. De La Cruz; Caridad N. Barrameda (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The study unveiled perceptions of school leaders and their expectations of millennial educators in terms of Drivers, Fit, Leadership Style and Culture, and Unconscious Biases with the endview of discovering an emerging leadership model for millennial educators. This employed explanatory-sequential design with two-phased, mixed-method approach. Results revealed that Drivers, Fit, Leadership Style and Culture, and Unconscious Biases and other leadership principles, school heads’ consideration of these domains lead to better commitment and performance of their leadership roles, while millennial teachers’ expectations of their school head’s role can guide current and aspiring school heads in managing a growing millennial generation of educators. Hereafter, six key elements appeared include Professional Instigation, Personal Provocation, Leadership Direction, Cultural Condition, Self-Predilection, and Organizational Acclimation. These emerging leadership principles upheld by millennial educators may be considered priorities of Professional Development Programs across all levels.